Mechanical Properties of Alkali-Treated Sugar Palm (Arenga Pinnata) Fiber Reinforced Epoxy Composites - Bachtiar, Dandi (2008)
The aims of this study is to determine the mechanical properties (tensile, flexural and impact properties) of Arenga pinnata fiber reinforced epoxy polymer composite after introduce the alkali treatment to the Arenga pinnata fiber. The fiber was treated by alkali solution with 0.25 M and 0.5 M NaOH solution for 1 hr, 4 hrs, and 8 hrs soaking time. The fiber was mixed with with epoxy and hardener at 10% of volume with long random type of fiber arrangement. Hand lay up process in this experiments were to produce specimen test. The mechanical properties of those fibers are 466.07 MPa for the tensile strength and 3.9 GPa for the modulus, the tensile strength of the pure epoxy is 69.39 MPa and 2.3 GPa for the modulus. Results from the tests show that the improving mechanical properties of Arenga pinnata fiber reinforced epoxy polymer were proven by using the alkali treatment. The ultimate tensile strength took place at 0.25 M NaOH solution with 1-hour soaking time, i.e. 49.875 MPa, an improvement of 16.4% from untreated composite. The tensile modulus at this condition gave the improvement of 13.6% from untreated fiber composite. The ultimate flexural strength also occurred at 0.25 M NaOH solution with 1 hour of soaking time, i.e 96.71 MPa, an improvement of 24.42% from untreated fiber composite. However, the ultimate flexural modulus happened at 0.5 M NaOH solution with 4 hours soaking time, i.e. 6948 MPa; on improvement of 148% from untreated composite. The ultimate impact strength of treated Arenga pinnata fiber reinforced epoxy composite took place at 0.5 M NaOH solution with 8 hours soaking time, i.e. 60 J/m with improving of 9.8% from untreated composite. The SEM analysis has been conducted to provide the analysis on interface adhesion between the surfaces of fiber with the matrix.